THE ORGANIZATION OF INDEPENDENT STUDENT TRAINING IN THE CREDIT MODULE SYSTEM AND ISSUES OF CREDIT POINT ACCUMULATION (SCIENCE TIME JOURNAL, 2026)
In this article, we will discuss the penetration of the credit-module system into higher educational institutions of the Republic of Uzbekistan, its positive aspects and important principles, the importance of independent work and study in the credit-module system, types and forms (in electronic form under the direct guidance of the teacher, under the guidance of the teacher, and the student himself is independent) of independent education, the purpose of Independent Education, the tasks of the student and teacher in independent education. In addition, we will also touch on the elements in the organization of independent work of students, forms of independent work and other topics.